Evaluasi Kepuasan Pengguna Sistem Informasi Perumahan (SIP PERKIM) Menggunakan Metode End-User Computing Satisfaction (EUCS) - Rizki, Mohammad; Sucipto, Hadi; Mashuri, Chamdan; Lazulfa, Indana (STIKOM Tunas Bangsa Pematangsiantar, 2026)
Sistem Informasi Perumahan (SIP PERKIM) is an online-based application used by Dinas Perumahan dan Permukiman Kabupaten Jombang to monitor the progress of physical development projects more effectively, accurately, and in real time. This study is aimed at measuring the level of user satisfaction with SIP PERKIM through the application of the End-User Computing Satisfaction (EUCS) method, which assesses satisfaction based on five main dimensions, namely Content, Accuracy, Format, Ease of Use, and Timeliness. The research employed a quantitative approach using a Likert-scale questionnaire distributed to all active SIP PERKIM users, totaling 30 Field Facilitators. The results of the validity and reliability tests indicate that all questionnaire items meet the criteria of validity and reliability, with a Cronbach’s Alpha value of 0.950. Descriptive analysis shows that all EUCS dimensions fall within the “Satisfied” category, with an overall average satisfaction score of 3.60. Furthermore, the results of the multiple linear regression analysis reveal that, simultaneously, all independent variables have a significant effect on user satisfaction, as indicated by the calculated F-value being greater than the F-table value. However, partially, only the Ease of Use and Format dimensions are found to have a significant influence on the satisfaction of SIP PERKIM users. These findings suggest that ease of use and the clarity and neatness of the system interface are the dominant factors shaping user experience.Although users were generally satisfied, several aspects still require improvement, particularly data consistency, system speed in displaying information, and the uniformity of report formats. This study is expected to serve as a basis for further development of SIP PERKIM to ensure it becomes more responsive, efficient, and aligned with user needs.